Examining the nature of the relationship between learners' conceptual understanding and their mathematical dispositions in the context of multiplication - Ndongeni, Siviwe Lungelwa (Rhodes University, Faculty of Education, Department of Education, 2014)
The focus of this study is to explore three key aspects of learners' multiplicative proficiency: the nature of learners' conceptual understanding of multiplication, the nature of learners' numeracy dispositions (in the context of learning multiplication), and the relationship between conceptual understanding and productive dispositions in the context of multiplication. The study used a qualitative case study approach to gather rich data in relation to these. In the study a purposively selected sample of six Grade 4 learners was used from the same school: two high, two average, and two low performers. Kilpatrick, Swafford, and Findell (2001) define conceptual understanding as a functional grasp of mathematical ideas and its significant indicator is being able to represent mathematical situations in different ways and knowing how different representations can be useful for different purposes. They then refer to productive disposition as the 'tendency to see sense in mathematics, to perceive it as both useful and worthwhile, to believe that steady effort in learning mathematics pays off, and to see oneself as an effective learner and doer of mathematics' (p.131). Individual interviews were conducted using Wright, et al.'s (2006) instrument for exploring the nature of students' conceptual understanding of multiplication. Wright, et al. (2006) argue that the topics of multiplication and division build on the students' knowledge of addition and subtraction, and also multiplication and division provide foundational knowledge for topics such as fractions, ratios, proportion and percentage, all of which are core and essential areas of mathematical learning typically addressed in the primary or elementary grades. Researchers agree that learners have to be exposed to various strategies so that they are able to see that there is a difference between additive reasoning and multiplicative reasoning. In order to classify learners' conceptual understanding of multiplication an analysis of the data was done and learners were allocated levels according to the Wright, et al. (2006) levels of achievement. For the classification of learner dispositions, the data was analysed in terms of the elements of productive disposition as defined by Kilpatrick, et al. (2001) and Carr and Claxton (2002). The key findings of the study indicate that for conceptual understanding most of the learners depended on using concrete materials in solving multiplication and they also used basic strategies and methods. The findings for productive dispositions were that most of the learners saw themselves as competent in doing multiplication but the aspect of sense making and steady effort was less developed. The findings for the relationship between conceptual understanding and productive disposition were that both strands have a mutual relationship in which one helped the other to develop.
Keywords: Multiplication -- Study and teaching (Elementary) -- South Africa; Mathematics -- Study and teaching (Elementary) -- South Africa; Problem solving in children; Multiplication -- Ability testing